2010
DOI: 10.1007/s11845-010-0538-7
|View full text |Cite
|
Sign up to set email alerts
|

Do Doppler waveforms at the common femoral artery accurately predict iliac stenosis?

Abstract: Whilst CFA waveform morphology is a useful adjunct in detection of iliac disease, normal triphasic waveforms do not exclude iliac stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The marginal PPV (65.22%) does not allow the use of an AHDU as a conclusive diagnostic test or facilitate mapping of arterial segments for further investigations and possible arterial interventions (angioplasty or bypass). 12,13 The limitations of our study include a medium-sized sample and relatively small number of subjects assessed for interrater reliability. However, the high positive LR shows that results are consistent and reproducible.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The marginal PPV (65.22%) does not allow the use of an AHDU as a conclusive diagnostic test or facilitate mapping of arterial segments for further investigations and possible arterial interventions (angioplasty or bypass). 12,13 The limitations of our study include a medium-sized sample and relatively small number of subjects assessed for interrater reliability. However, the high positive LR shows that results are consistent and reproducible.…”
Section: Discussionmentioning
confidence: 94%
“…The marginal PPV (65.22%) does not allow the use of an AHDU as a conclusive diagnostic test or facilitate mapping of arterial segments for further investigations and possible arterial interventions (angioplasty or bypass). 12,13…”
Section: Discussionmentioning
confidence: 99%
“…Normal patients have an arterial signal that is triphasic but this signal becomes progressively biphasic and then monophasic when the vessel is calcified, because of loss of recoil in the arterial wall. In a retrospective study of MRAverified iliac artery stenosis, abnormal Doppler waveforms (monophasic/biphasic) were found in 86% of patients, with a sensitivity of 86%, but specificity was only 57% (65). Other authors use only monophasic signals as their definition of abnormal to increase specificity (26).…”
Section: Synopsismentioning
confidence: 99%
“…When arteriography was used as a reference method, visual assessment of Doppler waveform in the common femoral arteries had high sensitivity, specificity, positive and negative predictive value for significant aorto-iliac stenoses or occlusions [9, 10]. However, in studies that used MR angiography as a reference method, the results were reported to be significantly worse [11, 12]. …”
Section: Introductionmentioning
confidence: 99%